Cooperation and discrimination within and across language borders: Evidence from children in a bilingual city - Silvia Angerer; Daniela Glätzle-Rützler; Philipp Lergetporer; Matthias Sutter (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2015)
We present experimental evidence from a bilingual city in Northern Italy on whether thelanguage spoken by a partner in a prisoner's dilemma game affects behavior and leadsto discrimination. Running a framed field experiment with 828 six- to eleven-year oldprimary school children in the city of Meran, we find that cooperation generallyincreases with age, but that the gap between cooperation among in-group members andcooperation towards children speaking another language is considerable and increasingwith age. This gap is due to both, in-group favoritism and language group discrimination.
Keywords: C91; C93; D03; 330; Cooperation; discrimination; language; children; experiment